2018
DOI: 10.1108/ijlss-08-2017-0092
|View full text |Cite
|
Sign up to set email alerts
|

CSFs for Six Sigma in service and manufacturing companies: an insight on literature

Abstract: Purpose This paper aims to identify and review the critical success factors (CSFs) for successful Six Sigma implementation in service and manufacturing companies given in published literature. Design/methodology/approach A descriptive evaluation of the literature body is followed by future research opportunities. Studies published on the topic of Six Sigma during 2005-2016 are reviewed to retrieve identified CSFs. Findings From published literature, 48 CSFs vital for Six Sigma implementation were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…The descriptive analysis shows the distribution of these articles with respect to year, theme, author, journal, authorship, geography, trend and author contribution to CSFs followed by the Pareto analysis that indulges two sets of CSFs. The conclusions of this study are consistent with the previous studies conducted by Ribeiro de Jesus et al (2016), Lande et al (2016), Antony et al (2018), Pathiratne et al (2018) and Sreedharan et al (2018). Table 6 represents the comparison of similar studies conducted across various countries.…”
Section: Discussionsupporting
confidence: 91%
“…The descriptive analysis shows the distribution of these articles with respect to year, theme, author, journal, authorship, geography, trend and author contribution to CSFs followed by the Pareto analysis that indulges two sets of CSFs. The conclusions of this study are consistent with the previous studies conducted by Ribeiro de Jesus et al (2016), Lande et al (2016), Antony et al (2018), Pathiratne et al (2018) and Sreedharan et al (2018). Table 6 represents the comparison of similar studies conducted across various countries.…”
Section: Discussionsupporting
confidence: 91%
“…Initiatives can also fail if poorly organized or monitored. One could argue that the structure assumptions defining the organization's LSS strategy are the most important success factors for any project (Pathiratne et al, 2018). In order to predict the outcome of LSS DMAIC activities, one must assume a project organizational support structure.…”
Section: Discussion: Structure Assumptionsmentioning
confidence: 99%
“…She summarised CSF using Pareto analysis and highlighted the 22 most referred CSF. Pathiratne et al (2018) observed that there is a huge disparity amongst CSF reported, and they range from 3 to 25 in different research works. Sreedharan et al (2018a) also used the Pareto analysis approach to summarise CSF for Lean, Six Sigma, LSS and TQM.…”
Section: Literature Reviewmentioning
confidence: 98%